Top 1% of all Frontiers Loop authors - Michael-Grigoriou, Despina (My University, 2026)
Despina Michael-Grigoriou ranks in top 1% of all Frontiers Loop authors, in ‘Views of Frontiers Articles’ impact benchmark, according to Frontiers, 2024, 2025, 2026. https://loop.frontiersin.org/people/873928/impact View Full Impact (login required) --> Benchmark Section: "Despina Michael-Grigoriou has more views of Frontiers articles than 99% of all Loop authors"
Keywords: World's Top Scientists